Seletividade de alguns agrotóxicos em uso na citricultura ao ácaro predador Neoseiulus californicus (McGregor) (Acari: Phytoseiidae) - Da Silva, Marcos Zatti [UNESP] (2006)
This work was carried out to determine the residual toxicity of the main pesticides used in citrus, on Neoseiulus californicus (McGregor) under laboratory conditions. For this, it was used the residual contact bioassay. Citrus leaves of the variety Pêra were sprayed in a Potter tower. The residual action was evaluated at 2 hours and 1; 3; 5; 7; 10; 14 e 21 days after treatment. Ten adult females of N. californicus were transferred to each ring, together with an enough amount of Tetranychus urticae nymphs and adults to feed the predator. Mortality evaluations were performed at 72 hours after treatment. Bioassays indicate that the pesticides: acrinathrin, deltamethrin, dinocap, sulphur, fenpropathrin, fenbutatin oxide and propargite were innocuous to N. californicus. On the other hand, abamectin, azocyclotin e cyhexatin caused mortalities of 29.8; 32.0 e 34.1%, respectively, two hours after transference. Dicofol, pyridaben and chlorfenapyr were extremely toxic to the predator mite, causing 100% of mortality two hours after the application. This way, to this population of N. californicus, the releases can be performed safely 3 days after the application, except for cyhexatin (5 days), dicofol and pyridaben (14 days) and chlorfenapyr (21 days), without risk of significant adult mortality rates due to the application of pesticides.